2004
DOI: 10.1103/physrevd.69.023001
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino signatures of the supernova: Gamma ray burst relationship

Abstract: We calculate the TeV-PeV neutrino fluxes of gamma-ray bursts associated with supernovae, based on the observed association between GRB 030329 and supernova SN 2003dh. The neutrino spectral flux distributions can test for possible delays between the supernova and the gamma-ray burst events down to much shorter timescales than what can be resolved with photons. As an illustrative example, we calculate the probability of neutrino induced muon and electron cascade events in a km scale under-ice detector at the Sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…For extended or slowly rotating stars, the jet may be unable to break through the envelope. Both penetrating (GRB producing) and 'choked' jets can produce a burst of approximately 5 TeV neutrinos by the interaction of accelerated protons with jet photons, while the jet propagates in the envelope (Mészáros & Waxman 2001;Razzaque et al 2004). The estimated event rates may exceed approximately 10 2 events per year in a kilometre-scale detector, depending on the ratio of non-visible to visible fireballs.…”
Section: (B ) Teraelectron Volt Neutrinosmentioning
confidence: 99%
“…For extended or slowly rotating stars, the jet may be unable to break through the envelope. Both penetrating (GRB producing) and 'choked' jets can produce a burst of approximately 5 TeV neutrinos by the interaction of accelerated protons with jet photons, while the jet propagates in the envelope (Mészáros & Waxman 2001;Razzaque et al 2004). The estimated event rates may exceed approximately 10 2 events per year in a kilometre-scale detector, depending on the ratio of non-visible to visible fireballs.…”
Section: (B ) Teraelectron Volt Neutrinosmentioning
confidence: 99%
“…GRB composition is greatly tied to two interesting topics: whether GRBs are the dominant sources of ultrahigh energy cosmic rays (UHECRs) [189,190] and high energy neutrinos [191,192,193]. These models all invoked a baryon-dominated outflow.…”
Section: Ejecta Compositionmentioning
confidence: 99%
“…When calculating the diffuse neutrino background from GRBs we assume that GRBs follow the star formation rate 3 . The diffuse neutrino flux on earth from GRBs distributed up to a redshift of z max can be expressed as,…”
Section: Diffuse Neutrino Spectra From Hl and Ll Grbsmentioning
confidence: 99%
“…The possibility of high energy neutrino emission from GRBs in the burst and the afterglow phases has been studied earlier by different groups [1,2,3,4]. It has been found that only the nearby high luminosity (HL) GRBs (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation